Magnetoresistive and Thermoresistive Scanning Probe Microscopy with Applications in Micro- and Nanotechnology - Meier, Tobias (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2014)
This work presents approaches to extend limits of scanning probe microscopy techniques towards more versatile instruments using integrated sensor concepts. For structural surface analysis, magnetoresistive sensing is introduced and thermoresistive sensing is applied to study nanoscale phonon transport in chain-like molecules. Investigating with these techniques the properties of shape memory polymers, a fabrication method to design application-inspired micro- and nanostructures is introduced.